Amplitude spectra of microseisms generated By cyclonic storms - SINGH , MATHURA; BHATTACHARYA, SN (MAUSAM, 1986)
The predominate periods of microseisms have been studied by spectral analysis of microseisms recorded at Kodaikanal and Poona generated by cyclonic storms. Amplitude spectra have been obtained when storms are at various depths over Bay of Bengal and Arabian Sea. Two types of microseisms are noticed; one in the period range from 9.10 to 9.71 sec and the other from 4.14 to 4.55 sec. It is interesting to note that the former belongs to primary microseisms having the same period as the ocean waves while the latter belongs to secondary microseisms with half the period of sea waves. It has also been found that the primary microseisms appear to be generated from storms over deep sea while the secondary microseisms are observed from storms both over shallow and deep water.